2007
DOI: 10.17759/chp.2007030403
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Time Perspective across Different Cultures: Review of Researches Using ZTPI Scale

Abstract: One's preference for certain time orientations is influenced by many factors including culture. The aim of this research was to describe the phenomenon of time perspective in different cultures. The authors carried out re-evaluation of reliability and validity of the Russian version of the Zimbardo Time Perspective Inventory (ZTPI) scale and compared the findings with the original scale as well as with its adapted versions (French and others). The sample consisted of 1136 people aged 14 to 81 from eighteen Rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Second, participants in the study consisted mostly of European American women enrolled in college, so the selected sample limits generalizability of the findings. Previous research has indicated sex and cross‐cultural differences in time perspectives (Andretta, Worrell, Mello, Dixson, & Baik, ; Ely & Mercurio, ; Mello & Worrell, ; Sircova et al, ; Zimbardo & Boyd, ). However, research examining sex differences in vocational identity status have not been found, and research examining cross‐cultural differences and similarities in vocational identity is lacking (Skorikov & Vondracek, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, participants in the study consisted mostly of European American women enrolled in college, so the selected sample limits generalizability of the findings. Previous research has indicated sex and cross‐cultural differences in time perspectives (Andretta, Worrell, Mello, Dixson, & Baik, ; Ely & Mercurio, ; Mello & Worrell, ; Sircova et al, ; Zimbardo & Boyd, ). However, research examining sex differences in vocational identity status have not been found, and research examining cross‐cultural differences and similarities in vocational identity is lacking (Skorikov & Vondracek, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on the relationship between culture-specific attitudes toward time and timed neuropsychological test performance in Russian and American participants. Although time attitudes have been identified as one of the potential sources of cultural influence on neuropsychological test results (Agranovich & Puente, 2007; Paul et al, 2007; Perez-Arce & Puente, 1996), and several surveys of time attitudes have been applied in cross-cultural settings (e.g., Block, Buggie, & Matsui, 1996; Rojas-Méndez, Davies, Omer, Chetthamrongchai, & Madran, 2002; Sircova et al, 2007), none of the existing measures have been specifically linked to timed neuropsychological test performance. Given that most North American neuropsychological instruments are timed (e.g., Camara, Nathan, & Puente, 2000; Rabin, Barr, & Burton, 2005), it is likely that cultural attitudes toward time may affect test results.…”
Section: Introductionmentioning
confidence: 99%
“…Different theoretical views of time perspective have emerged over the past three decades. The theory that has arguably garnered the most attention, however, is the one proposed by Zimbardo and colleagues (e.g., D’Alessio et al [2003], Sircova et al [2007], Stolarski et al [2015], Zimbardo and Boyd [1999] and Zimbardo et al [1997]). Zimbardo’s theoretical model posits the existence of five different time perspectives, each of which are simultaneously present (in differing amounts) in an individual, with one perspective typically being dominant over the others.…”
Section: Literature Reviewmentioning
confidence: 99%